RESEARCH AND DEVELOPMENT PROJECTS FOR DIGITAL AGRICULTURE IN POLAND - Katarzyna Kosior (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2023)
The aim of the article was to present a systematic review of research and development projects that included research tasks and proposals relevant to digitalization of agriculture in Poland. The transformation towards digital agriculture is currently one of the most important developmental challenges facing farms in Poland. The use of digital technologies and smart devices designed to optimize agricultural production and farm management processes is no longer just a matter of choice, but a necessity determined by the need to achieve climate, environmental and sustainable development goals. Research and development works carried out in the wide agri-food innovation ecosystem are of fundamental importance for the prospects of exploiting the opportunities offered by the current technological and digital revolution. However, information on ongoing and past research and development projects financed from the public funds is dispersed. The conducted review shows that although the number of projects and actions that support digital transformation in the Polish agricultural sector has increased in recent years, their scope remains limited. There is an insufficient number of interdisciplinary projects that encompass not only technological, but also socio-economic aspects of digitalization processes. Taking into account the need to both accelerate digital transformation in agriculture and to promote responsible research and innovation practices, it would be advisable to increase outlays for research and development projects that would support digitalization of Polish farms in holistic and systemic ways.